The foundations of next generation attention‐deficit/hyperactivity disorder neuropsychology: building on progress during the last 30 years. (December 2014) - Sonuga‐Barke, Edmund J.S.; Coghill, David
Preamble In the JCPP Virtual Issues series, editors are invited to look back over our catalogue and identify papers that illustrate the journal's influence on the emergence of specific fields within the broader domains of child psychology and psychiatry. This virtual issue1, 2 focuses specifically on the last 30 years of attention‐deficit/hyperactivity disorder (ADHD) research. While the journal has published papers on nearly every aspect of this condition our initial scoping exercise highlighted a particular impact in two areas: neuropsychology and behavioural genetics. Here we address the JCPPs contribution to contemporary understanding of the neuropsychology of ADHD. We are planning to put together a further Virtual Issue on behavioural genetics in the near future.